Building research capacity for sickle cell disease in Africa: Lessons and challenges from establishing a birth cohort in Tanzania - Nkya, Siana; Njiro, Belinda J.; Ngowi, Doreen; Solomon, David; Kaywanger, Frida; Nyangasa, Salama; Ndoje, Godfrey; Marco, Emmanuela; Moses, Mazoea; Makani, Julie (Frontiers in Pediatrics, 2022)
Sickle Cell Disease (SCD) is a known public health burden in sub-Saharan Africa. The manifestation of SCD starts in early childhood and if not well managed may lead to early death (before the age of five years). Understanding the underlying mechanisms that influence early SCD manifestation is of great importance for early disease and intervention management which will in turn, reduce both morbidity and mortality rates in children. One approach to achieving this is by establishing SCD birth cohorts that can be followed for a period of time (3-5 years) whilst documenting necessary information related to early childhood illnesses. To date, there are few SCD birth cohorts in Africa. To address this gap, we have established a birth cohort of babies with SCD and without SCD (with sickle cell trait and healthy babies). These babies are followed up for three years coupling their study visits with their immunization schedule. During enrolment and follow-up visits, information on demographic, clinical and laboratory parameters are collected. To date, we have enrolled a total of 341 babies with and without SCD. Out of these, a total of 311, 186, 133, 81, 44 and 16 babies have returned for their 1st, 2nd, 3rd, 4th, 5th and 6th visits, respectively. We have collected both demographic and clinical information for these babies at enrollment and follow-up. We have also archived samples for genomic studies which is the focus of this cohort. In addition, we have utilized this platform to learn on the best approaches of establishing and maintaining a research birth cohort in an African context. We have analyzed the practical issues pertaining to the integration of the birth cohort with the immunization platform which seems to be the most effective and sustainable strategy in maintaining a birth cohort in our context.